Urbanization, transportation infrastructure, ICT, and economic growth: A temporal causal analysis. (August 2021) - Pradhan, Rudra P.; Arvin, Mak B.; Nair, Mahendhiran
Abstract: In many countries, urbanization is seen as an important policy tool to ensure sustained economic growth. While urbanization can lead to positive economic outcomes, unfettered migration into urban areas without appropriate infrastructure support such as information and communication technology (ICT) infrastructure and transportation infrastructure can lead to negative side effects such as congestion, formation of slums, and other diseconomies of scale. The latter can actually lower economic growth. This study examines the relationships between urbanization, transportation infrastructure, ICT infrastructure, and economic growth in the G-20 countries from 1961 to 2016. Using the panel vector error-correction model, the study shows that there is a myriad of temporal causal relationships between the four variables in both the short and long run. The key policy implication of these results is that long-run economic growth in the G-20 countries depends on the co - development of policies in creating a vibrant urban ecosystem that is enabled by intelligent transportation systems and underpinned by a sound ICT infrastructure plan. Graphical abstract: Note 1 : PEG is the per capita economic growth; TRA is transportation infrastructure; ICT is information and communication technology infrastructure; and URB is urbanization. Arrows indicate possible causal links. Note 2 : H1A, B : Transportation infrastructure Granger-causes economic growth and vice versa. H2A, B : ICT infrastructure Granger-causes economic growth and vice versa. H3A, B : Urbanization Granger-causes economic growth and vice versa. H4A, B : Transportation infrastructure Granger-causes ICT infrastructure and vice versa. H5A, B : Transportation infrastructure Granger-causes urbanization and vice versa. H6A, B : ICT infrastructure Granger-causes urbanization and vice versa. Unlabelled Image Highlights: Linkages among urbanization, transportation and ICT infrastructure, and economic growth are considered. The sample comprises G-20 countries over 1961-2016. Panel vector error-correction model is used to examine causality. Temporal causality runs from the covariates to economic growth in the long run. Short-run results depend on the specific measure of ICT infrastructure utilized.